Advancing neutron imaging techniques to highest resolution with fluorescent nuclear track detectors - Abdul Muneem; Junya Yoshida; Takehiko R. Saito; Hiroyuki Ekawa; Masahiro Hino; Katsuya Hirota; Go Ichikawa; Ayumi Kasagi; Masaaki Kitaguchi; Kenji Mishima; Jameel-Un Nabi; Manami Nakagawa (Scientific Reports)
Abstract Neutron imaging is a nondestructive and noninvasive inspection technique with a wide range of potential applications. However, the fundamentals of this technique still need to be improved, one of which involves achieving micrometer scale or even better resolution, which is a challenging task. Recently, a high-resolution neutron imaging device based on fine-grained nuclear emulsions was developed. Although these detectors demonstrate exceptionally high resolutions, they have several limitations. Furthermore, these detectors require an additional chemical development process and are thus not reusable. To overcome these limitations, we investigated whether neutron imaging devices based on fluorescent nuclear track detectors were suitable for high-resolution neutron imaging. Fluorescent nuclear track detectors are reusable solid-state detectors that do not require additional chemical processing. A novel technique combining neutron imaging based on fluorescent nuclear track detectors with a neutron converter layer formed using $$^{10}$$ B $${_4}$$ C was developed with unprecedented resolution. The neutron imaging of a gadolinium-based grating with a periodic structure of 9 $$\upmu$$ m was performed using the proposed fluorescent nuclear track detector-based neutron imaging device, and the grating structure was successfully resolved. The measured resolution was 0.887 ± 0.009 $$\upmu$$ m, which is the 1 $$σ$$ 10–90% edge response obtained using optical images of the fluorescent nuclear track detectors.